Perlindungan Korban dalam Penanganan Post Traumatic Stress Disorder pada Tindak Kejahatan Bullying pada Remaja di Indonesia - Ananda Ima Saputri; Ridwan Arifin (Jurnal Aktual Justice, 2022)
This writing aims to determine the impact of bullying crime from the point of view of victims of bullying who get stressed post-traumatic stress disorder so that victims need to get protection from the incident. In the 1945 Constitution article 28B (paragraph 2) it has been explained that: "Every child has the right to survival, growth and development, and is entitled to protection from violence and discrimination". But in fact, this crime of bullying is increasingly widespread by not seeing the opponent as material for consideration of reducing the effects of the crime he committed. Bullying itself has been happening for a long time and seems to be part of the culture of community social behavior both at school and in the environment at home. Victims also generally have feelings of being helpless, afraid, and threatened because they experience forms of intimidation such as threatening, spreading rumors, taunting, cursing, and alienating someone from a group whether done directly or through technology is an example of bullying. The act of bullying is considered only part of the way children play, even though the impact of this action greatly affects the psychological health of its victims. In addition, Bullying has a negative impact on mental health and well-being of adolescents so that parents, school teachers, and the government should pay more attention to victims of bullying and do not just look at the nature of the crime. Protection of victims of bullying needs to be given more attention, improved, and taught early on to children whose development is in the process of becoming adults so that the state can minimize bullying that occurs wherever someone lives. And victims of the impact of bullying can be reduced every year.